Transformasi Digital Riset Pemasaran Global dengan Integrasi Teknologi Terkini untuk Menyusun Strategi Responsif terhadap Perubahan Pasar Global - Suhairi; Nurhazizah; Syanda, Syahla; Nasution, Riska Arianti (Ikatan Da'i Indonesia, 2024)
This research explores the impact of digital transformation on data collection and analysis, as well as responsive strategies to changes in the global market. The findings indicate that companies adopting Big Data Analytics gain access to unprecedented volumes of data, including transaction data, customer interactions, and social media information, allowing for a deeper understanding of consumer behavior. The integration of current technologies not only pertains to data collection but also influences the implementation of marketing strategies. Responsive strategies to changes in the global market require a profound understanding of factors influencing consumer behavior, and modern technology enables companies to shift towards a robust data-driven approach. In conclusion, companies need to focus on developing their team's skills in managing current technologies to maximize the benefits of the global marketing research transformation and maintain competitiveness in the ever-evolving global market.